Analisis Studi Kelayakan Usaha Briket Limbah Tongkol Jagung - Delfitriani, Delfitriani; Dzulfiqar, Akram; Ariyanto, Dodik (JURNAL AGROINDUSTRI HALAL, 2024)
The use of energy resources that are not environmentally friendly is a problem in Indonesia today. Briquettes are also the primary material because they are abundant, and the primary material has yet to be optimally utilized, including corn cobs. The purpose of this study is to analyze the economic feasibility of corn cob waste briquettes in this study using data analysis of technological technical aspects, financial feasibility analysis such as Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR) and Benefit and Cost Ratio (B/C). The results showed that it takes 19,800 kg of corn cobs to produce charcoal, as much as 3,168 kg and 158.4 kg with tapioca starch adhesive material, as much as 5% of the total weight of charcoal powder, requiring four pieces of equipment, namely pyrolyzer machines, Hammer mills, Planetary mixers, and Tray dryers. Furthermore, the feasibility analysis of this corn cob briquette business was declared feasible with the four categories: Payback Period (PP) for 3.1319 years, Net Present Value (NPV) of Rp 28,129,336,212; IRR of 17.77%, and Net B/C of 1.55. The corn cob briquette agro-industry will remain profitable even if the production capacity decreases by 28% from the original capacity. The agro-industry can also still operate despite an 8% decrease in the selling price of briquettes and will remain profitable if raw materials increase by 17%.